MicroRNA-495 inhibits proliferation of glioblastoma multiforme cells by downregulating cyclin-dependent kinase 6 - Chen, Shu-Mei (BioMed Central, 2013)
BACKGROUND: Glioblastoma multiforme (GBM) is the most aggressive type of glioma and carries the poorest chances of survival. There is therefore an urgent need to understand the mechanisms of glioma tumorigenesis and develop or improve therapeutics. The aim of this study was to assess the possible prognostic value of cyclin-dependent kinase 6 (CDK6) and the effects of microRNA-495 (miR-495) manipulation on CDK6 expression and cell survival in glioma cells. METHODS: Analyses of clinical specimens from GBM patients were used. Expression of CDK6 was analyzed by real-time polymerase chain reaction (RT-PCR), Western blotting, and immunohistochemistry. Expression of CDK6 was also analyzed after over-expression of miR-495 in T98 cells; both cell proliferation and RB phosphorylation were examined. Cell proliferation, cell cycle distribution, and RB phosphorylation were also examined after knockdown of CDK6 in U87-MG and T98 cells. RESULTS: Analyses of clinical specimens from GBM patients identified that CDK6 is significantly expressed in gliomas. CDK6 antigen expression was higher in tumor cores and margins than in adjacent normal brain tissues, and higher levels of CDK6 expression in the tumor margin correlated with decreased survival. Over-expression of miR-495 in T98 cells downregulated the expression of CDK6 and inhibited retinoblastoma phosphorylation, and knockdown of CDK6 in U87-MG and T98 cells by siRNAs resulted in cell cycle arrest at the G1/S transition and inhibition of cell proliferation. CONCLUSIONS: This study revealed miR-495 is down-regulated in glioma tissues. Furthermore, miR-495 regulated CDK6 expression and involved in glioma cell growth inhibition, which indicated the possible role of miR-495 in tumor progression.